Building a functional national One Health platform: the case of Tanzania - Andrew Y. Kitua; Susan Scribner; Mark Rasmuson; Dominic Kambarage; Janneth Mghamba; Elibariki R. Mwakapeje; Harrison Chinyuka; Jubilate Bernard; Kate Zimmerman; Sambe Duale; David Mutonga (BMC, 2019)
Abstract Background The USAID Preparedness and Response (P&R) project's publication on Multisectoral Coordination that Works identified five dimensions most critical to creating effective and sustainable One Health platforms: political commitment, institutional structure, management and coordination capacity, technical and financial resources, and joint planning and implementation. This case study describes Tanzania experience in using these dimensions to establish a functional One Health platform. The main objective of this case study was to document the process of institutionalizing the One Health approach in Tanzania. Methods An analysis of the process used to establish and institutionalize the MCM in Tanzania through addressing the five dimensions mentioned above was conducted between August 2018 and January 2019. Progress activity reports, annual reports and minutes of meetings and consultations regarding the establishment of the Tanzania national One Health platform were examined. Relevant One Health publications were studied as reference material. Results This case study illustrates the time and level of effort required of multiple partners to build a functional multi-sectoral coordinating mechanism (MCM). Key facilitating factors were identified and the importance of involving policy and decision makers at all stages of the process to facilitate policy decisions and the institutionalization process was underscored. The need for molding the implementation process using lessons learnt along the way -- "sailing the ship as it was being built" -- is demonstrated. Conclusions Tanzania now has a functioning and institutionalized MCM with a sound institutional structure and capacity to prevent, detect early and respond to health events. The path to its establishment required the patient commitment of a core group of One Health champions and stakeholders along the way to examine carefully and iteratively how best to structure productive multisectoral coordination in the country. The five dimensions identified by the Preparedness and Response project may provide useful guidance to other countries working to establish functional MCM.